Species Diversity Induces Idiosyncratic Effects on Litter Decomposition in a Degraded Meadow Steppe - Naeem, Iqra; Asif, Talal; Wu, Xuefeng; Hassan, Nazim; Yiming, Liu; Wang, Hongjun; Wang, Ling; Wang, Deli (Frontiers in Environmental Science, 2021)
Litter decomposition is a fundamental path for nutrient cycling in a natural ecosystem. However, it remains unclear how species diversity, including richness and evenness, affects the decomposition dynamics in the context of grassland degradation. Using a litter bag technique, we investigated the litter-mixing effects of two co-existing dominant species (Leymus chinensis Lc and Phragmites australis Pa), as monocultures and mixtures with evenness (Lc:Pa) from M1 (30:70%), M2 (50:50%), and M3 (70:30%), on decomposition processes over time (60 and 365 days). The litter bags were placed on the soil surface along a degradation gradient (near-pristine (NP), lightly degraded (LD), and highly degraded (HD)). We found that (1) mass loss in mixture compositions was significantly and positively correlated with initial nitrogen (N) and cellulose contents; (2) litter mixing (richness and evenness) influenced decomposition dynamics individually and in interaction with the incubation days and the degradation gradients; (3) in GLM, non-additive antagonistic effects were more prominent than additive or neutral effects in final litter and nutrients except for carbon (C); (4) in nutrients (C, N, lignin) and C/N ratio, additive effects shifted to non-additive with incubation time. We speculated that the occurrence of non-additive positive or negative effects varied with litter and nutrients mass remaining in each degraded gradient under the mechanism of initial litter quality of monoculture species, soil properties of experimental sites, and incubation time. Our study has important implications for grassland improvement and protection by considering species biodiversity richness, as well as species evenness.